2020
DOI: 10.1007/s10484-020-09477-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Effectiveness of HRV-Biofeedback and Mindfulness for Workplace Stress Reduction: A Randomized Controlled Trial

Abstract: Psychophysiological disorders due to work-related stress continue to be highly costly for health systems and approaches for cost-effective and easily accessible interventions are much needed. Both heart rate variability-biofeedback (HRV-Bfb) and mindfulness-based interventions (MBI) have been empirically shown to reduce stress. This study compares these two interventions in the work context to a wait-list-control-group (WLC). In this three-armed randomized controlled trial (RCT), 69 healthy adults employed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 67 publications
(90 reference statements)
2
28
0
9
Order By: Relevance
“…Among the studies, two were conducted in Taiwan 35 , 43 , two in Netherlands 44 , 47 , three in the USA 26 , 46 , 54 , three in Germany 45 , 49 , one in the UK, one in Austria, one Iran and one in Sweden 48 , 50 , 51 , 53 . Nine studies were conducted on patients with cardiovascular disease, stress symptoms, cancer or alcohol disorder, while the remaining five studies focused on non-clinical samples 26 , 44 , 47 , 48 , 52 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies, two were conducted in Taiwan 35 , 43 , two in Netherlands 44 , 47 , three in the USA 26 , 46 , 54 , three in Germany 45 , 49 , one in the UK, one in Austria, one Iran and one in Sweden 48 , 50 , 51 , 53 . Nine studies were conducted on patients with cardiovascular disease, stress symptoms, cancer or alcohol disorder, while the remaining five studies focused on non-clinical samples 26 , 44 , 47 , 48 , 52 .…”
Section: Resultsmentioning
confidence: 99%
“…One of the most popular therapies is Acceptance and Commitment Therapy (ACT) [ 64 ]. In most trials ACT is reported to be superior or equally effective as cognitive behavioral therapy [ 65 ].Maybe it would be more efficient for our health system to integrate psychophysiology like ACT, HRV-Biofeedback and mindfulness in treatment of depression, PTSD, and anxiety disorders, because of the efficacy, more self-control of the client, and lowering the cost of treatment [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 A recent randomised control trial (RCT) highlighted significant challenges of applying both heart rate variability-biofeedback (HRV-Bfb) and mindfulness-based interventions (MBI) in a workplace context. 17 …”
Section: Introductionmentioning
confidence: 99%